(untitled) (LEGAL DIALOGICA, 2025)
This study aims to determine the Judge’s legal considerations in deciding the case of Decision Number 3/Pid.Sus-TPK/2019/PN.Bgl against Corporations. To determine the implementation of Supreme Court Regulation Number 13 of 2016 concerning procedures for handling criminal cases by corporations in Decision Number 3/Pid.Sus-TPK/2019/Pn.Bgl, this study uses a normative juridical legal research method with a focus on analyzing primary and secondary data using qualitative data analysis techniques. The results of this study indicate that (1). In Decision Number 3/Pid.Sus-TPK/2019/PN.Bgl, the judge’s legal considerations regarding corporations emphasize that although corporations are not physically living legal entities, they can be held criminally liable if the elements of a criminal act are met through their management or corporate organs. The judge considered evidence of active involvement of management in corruption that harms state finances and benefits the corporation. (2) In the application of Supreme Court Regulation Number 13 of 2016 in Decision Number 3/Pid.Sus-TPK/2019/PN.Bgl, the Public Prosecutor (JPU) successfully implemented Supreme Court Regulation Number 3/Pid.Sus-TPK/2019/PN.Bgl. The Supreme Court (Perma) Regulation No. 13 of 2016 was applied by proving that corporations meet the elements of criminal liability, such as control by management and profits for the corporation. The panel of judges accepted the prosecutor’s argument, thus proving the Supreme Court Regulation effective as a legal basis for prosecuting corporations in corruption cases. This research recommendation calls for clear and firm benchmarks or criteria for corporate criminal liability. Law enforcement needs to delve deeper into the internal structure and oversight system of corporations in proving corporate wrongdoing, so that criminal liability is not based solely on individual actions. Furthermore, the implementation of compliance programs at the corporate level is needed to prevent systemic corruption. Corporations found guilty of corruption need to be subject to strict and transparent sanctions, including maximum fines, suspension of business licenses, or termination of contracts with the state. Abstrak: Penelitian ini bertujuan Untuk mengetahui Pertimbangan hukum Hakim Dalam Memutuskan Perkara putusan Nomor 3/Pid.Sus-TPK/2019/PN.Bgl terhadap Korporasi. Untuk mengetahui Penerapan Perma Nomor 13 Tahun 2016 tentang tata cara penanganan perkara tindak pidana oleh korporasi Dalam Perkara Putusan Nomor 3/Pid.Sus-Tpk/2019/Pn.Bgl . Penelitian ini menggunakan metode penelitian hukum yuridis Normatif dengan berfokus menganalisis data primer dan data sekunder menggunakan teknis analisis data kualitatif. Hasil Penelitian Ini menunjukkan Bahwa (1). Dalam Putusan Nomor 3/Pid.Sus-TPK/2019/PN.Bgl, pertimbangan hukum hakim terhadap korporasi menekankan bahwa meskipun korporasi bukan subjek hukum yang hidup secara fisik, namun dapat dimintai pertanggungjawaban pidana jika memenuhi unsur perbuatan pidana melalui pengurus atau organ korporasi. Hakim mempertimbangkan adanya bukti keterlibatan aktif pengurus dalam tindak pidana korupsi yang merugikan keuangan negara serta adanya keuntungan bagi korporasi, (2). Penerapan Perma Nomor 13 Tahun 2016 dalam Putusan Nomor 3/Pid.Sus-TPK/2019/PN.Bgl, Jaksa Penuntut Umum (JPU) berhasil menerapkan Perma No. 13 Tahun 2016 dengan membuktikan bahwa korporasi memenuhi unsur pertanggungjawaban pidana, seperti adanya kendali dari pengurus dan keuntungan bagi korporasi. Majelis hakim menerima argumentasi JPU, sehingga Perma tersebut terbukti efektif sebagai dasar hukum dalam menjerat korporasi dalam perkara tindak pidana korupsi. Rekomendasi Penelitian Ini perlunya pengaturan tolak ukur atau kriteria pertanggungjawaban pidana korporasi dengan jelas dan tegas, Penegak hukum perlu lebih mendalami aspek struktur internal dan sistem pengawasan korporasi dalam membuktikan kesalahan korporasi, agar pertanggungjawaban pidana tidak hanya didasarkan pada tindakan individu. Selain itu, perlu penguatan penerapan compliance program di tingkat korporasi untuk mencegah tindak pidana korupsi secara sistemik. Serta Korporasi yang terbukti melakukan tindak pidana korupsi perlu diberikan sanksi yang tegas dan transparan, baik berupa denda maksimal, pembekuan izin usaha, maupun pemutusan kontrak dengan negara.